Investigating the evolution of sensory processing disorders and their role in the development of psychopathology - Monteiro, Maria do Rosário (2025)
Introduction: Sensory processing disorder (SPD), as outlined in the Diagnostic Classification of Mental Health and Developmental Disorders of Infancy and Early Childhood (DC: 0-5), is characterized by behavioral patterns of atypical responses to sensory stimuli in infants and young children, which can significantly impact the child’s daily functioning. While SPD is recognized as potentially co-occurring with physiological challenges and as a precursor to future difficulties, there is limited understanding of how the condition evolves into other diagnostic categories over time. The aim of this study was to longitudinally characterize the progression of children diagnosed with SPD and their transition to the development of other psychopathological conditions. Methods: Ninety children aged 1 to 5 years diagnosed with regulation disorders of sensory processing (RDSP) according to the DC:0-3R classification system in use at the time were included between 2008 and 2014. Sociodemographic data were collected at the time of diagnosis and during follow-up, and a comprehensive overview of the evolving diagnostic categories for each patient over the years based on the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) criteria, was provided. Results: The retrospective analysis revealed that, at the time of diagnosis, 60% of the children had global developmental delay and 24.5% had comorbid diagnoses. During follow-up, most children (64.4%) were diagnosed with attention-deficit/hyperactivity disorder (ADHD), followed by 17.8% with intellectual developmental disorder and 13.3% with autism spectrum disorder. Discussion: Although a causal relationship was found only between the impulsive type of RDSP and ADHD, this study highlights the high prevalence of psychiatric disorders in children with a history of sensory regulation difficulties. The findings underscore the need for larger and more diverse studies to draw robust conclusions and better understand these associations.